Adherence to pediatric acute chemotherapy‐induced nausea and vomiting guidelines in Canadian hospitals. Issue 1 (14th October 2018) - McKinnon, Krista; Jupp, Jennifer; Ghosh, Sunita; Digout, Carol; Eason, Stephanie; Romanick, Marcel
Abstract: Background: Chemotherapy‐induced nausea and vomiting (CINV) impacts quality of life for patients. Guidelines for emetogenicity classification and prevention of CINV in children were recently published and endorsed by pediatric oncology organizations. Procedure: A multicenter chart review was performed at four Canadian pediatric oncology centers examining rates of prescribing adherence to CINV guidelines between January 2012 and December 2015. Eligible patients received their first chemotherapy course of highly emetogenic chemotherapy (HEC) or moderately emetogenic chemotherapy (MEC). Results: Guideline adherence was described in 204 patients as antiemetic‐only guideline adherence (AGA; examined medication/class prescribed only) and complete guideline adherence (CGA; examined medication/class, dose, frequency, and duration prescribed). Adherence was 29% (HEC 30%, MEC 19%, P  = 0.1) and 2% for AGA and CGA patients, respectively. Vomiting in the first 24 h was experienced by 24% of AGA and 34% of non‐AGA patients ( P  = 0.13), with mean breakthrough medication doses similar between AGA and non‐AGA groups (HEC 1.8 vs 1.5, P  = 0.45; MEC 3 vs 1.42, P  = 0.35). In the first 24 h, HEC AGA patients achieved a complete control rate of 37% vs 45% for non‐AGA patients ( P  = 0.31), while patients receiving AGA therapy for MEC achieved a complete control rate of 80% vs 24% for non‐AGA patients ( P  = 0.02). Conclusions: Adherence to guidelines was low across all four pediatric institutions. Each center used different approaches to implement pediatric CINV guidelines. Complete CINV control was low, with reports of emesis high, indicating that patients are not receiving optimal treatment.